Vegetation cover and land use of a protected coastal area and its surroundings, southeast Brazil - Caris,Elisa Araujo Penna (2013)
We applied remote sensing techniques on a TM Landsat 5 image (1:50,000) to map land use and vegetation cover of the Restinga de Jurubatiba National Park and surroundings. The thematic map generated from the digital classification of the image allowed us to spatially characterize and quantify the different land uses and soil covers of the area. Thirteen classes were identified. The most representative classes in the park were the Clusia (31.99%) and Ericaceae formations (29.14%). More than 90% of the park is occupied by native vegetation and coastal lagoons. The surroundings are very much altered by human activities (e.g. 70.64% is used for agriculture and/or cattle raising). Two hundred and three forest fragments (0.3 to 235 ha) were identified, of which 45.3% are less than 5 ha. Most fragments (56.7%) have a very elongated shape, and are thus submitted to an intense edge effect. The intense fragmentation of the surroundings and the isolation of this protected area can imply, in the long run, the loss of genetic diversity.